FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI PENERTIBAN PEDAGANG KAKI LIMA (PKL) DI JALAN HR. SUBRANTAS KOTA PEKANBARU - Febra Arnita Nasution; Chalid Sahuri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Jalan HR. Subrantas is one of main streets in Pekanbaru that connects Riau Province, West Sumatera Province, and North Sumatera Province. The existence of this street is important for visitors to know more about icons in Pekanbaru, especially Islamic State University Sulthan Syarif Qosim, University of Riau, Tampan Nuthouse, Panam’s Awal Bross Hospital, etc. Consequently, this street has to confer impression of control and ecofriendly in order to make every single visitors who come to Pekanbaru get good experience. However, the condition of this street is unlikely what it is expected. There are some street vandours (Pedagang Kaki Lima) on the side of the street. It implies that the regulation of Pekanbaru City is not yetproperlyfollowed. Hence, the researcher is interested in doing a reseach about how the street vandours should be controlled on Jalan HR. Subrantas, Pekanbaru City.The concept that is used in this research is implementation that is told by Van Metter and Van Horn. According to them, there are a few factors that affects the policy to be followed properly, such as: standard and policy’s targets, resources, the communication between organization and implementator agency, the condition of sosial economy politics, and implementor’s disposisions. The objectives of this research is to analyze the cause of street vandours operate in the side of the street, and the way to implement regional policy (Perda) No. 5 year 2002 effectively. The method that was used in this reseach is descriptive method. The data collection technique is interviewing, observation, and documentation with purposive sampling method as the information and the data analysis with triangular technique.The result of this research shows that the control of street vandours at Jalan HR. Subrantas is not yet done maximally because of the restrictiveness of human resources and facilities and infrastructures. The reason why the street vandours in Jalan HR. Subrantas do not want to move to other location that is prepared by governmentis that the location is unlike what they expected.Keywords: Street vandours, Implementation, Jalan HR. Subrantas